Implementation of Social Media in ITSM Processes - Benita BELÁŇOVÁ; Anna HAMRANOVÁ (Communications of International Proceedings, 2021)
The paper deals with the role of the human factor in the management of IT services (ITSM). Within ITSM, it is focused on the area of communication and especially on the use of social media. It contains an overview of the analyzed literature, on the basis of which a research model was created, as well as the results of a questionnaire survey in Slovak companies. The aim of the research was to find out the approach of companies to the use of social media in the work process. Standard methods of scientific work were used in the processing of the paper: analysis, synthesis, comparison and selection. A questionnaire survey was used to obtain data, which was evaluated using descriptive statistics and cluster analysis. The results of the research confirmed that in companies operating in Slovakia, only a certain part of employees use social media for work communication, while it is mostly informal communication. Support of top management, as well as the level of experience gained based on information from social media, is at an average level. The quality of the obtained information was evaluated the worst. Large companies, in dominant foreign ownership, mostly support the use of social media. Surprisingly, medium-sized companies of foreign owners declared the worst approach. Regarding opinions on the future of social media use in companies, only 23% of respondents predict their active use, most are convinced that social media will be used only as complementary tools. This fact does not coincide with trends published in the literature.
Keywords: IT Service Management (ITSM); Communication; Social Media; Social Networks